Rule of experts : Egypt, techno-politics, modernity - Mitchell, Timothy, 1955- (University of California Press, 2002)
In a series of interrelated essays focused on twentieth-century Egypt, the author, a political theorist, provides an examination of the forms of reason, power and expertise that characterize contemporary politics.